Hydrologic-Hydraulic Dimensioning of Road Drainage Systems - Violeta Gjesovska (My University, 2019)
Traffic safety depends on many factors, but primarily on the quality of the designed and constructed roads, as well as their maintenance during the period of exploatation. In the phase of road design and, certainly, in the period of exploatation, one of the key elements of traffic safety is well designed and constructed roads in accordance with the applicable norms for road design. One of the stages of road design that has a major impact on the quality of roads and the degree of traffic safety is drainage. Drainage includes several segments: (1) quick and smooth drainage of the pavement surface from atmospheric precipitation in order to ensure traffic on dry roads, (2) drainage of surface waters from the surrounding basin areas that gravitate towards the carriageway in order to prevent flooding and/or damage to the roads under the influence of surface waters; and (3) drainage of underground waters from the road foundation zone in order to prevent unwanted damage to the carriageway under the influence of underground waters. These drainage systems, their proper design and dimensioning according to hydrological-hydraulic calculations as well as their maintenance in the exploitation stage are the subject of this paper.
Keywords: hydrological-hydraulic dimensioning, drainage, safety, roads